Penerapan Pendekatan Cooperative Learning Tipe Jigsaw untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PKn di SD Negeri 25 Mataram - Rauhun Rauhun (Jurnal Paedagogy, 2022)
This study aims to increase students' learning motivation by using the Jigsaw Cooperative Learning approach in Civics subjects at SDN 25 Mataram. This research method is classroom action research with the research subject being class VI with 37 students. The instrument of this research used observation sheets and tests. While the data analysis technique used quantitative and qualitative descriptive analysis. The results showed that the teacher's observations from cycle I (61.25) in cycle II increased to (77.5), the results of observations of student learning motivation in cycle I (41.67) in cycle II increased (81.25), and the results of observations of student learning activities in cycle I (56.25) in the second cycle increased (81.25). So that it can be concluded that the application of the jigsaw type of cooperative learning approach has been able to increase student learning motivation which has an impact on student learning outcomes in Civics subjects.